2006
DOI: 10.1016/j.amjcard.2006.03.045
|View full text |Cite
|
Sign up to set email alerts
|

Relation of C-Reactive Protein and Tumor Necrosis Factor-Alpha to Ambulatory Blood Pressure Variability in Healthy Adults

Abstract: Elevated blood pressure (BP) variability has been linked to an increased risk of adverse cardiovascular events, but the biological factors which promote elevated BP variability are not entirely understood. We conducted a cross-sectional study to examine whether inflammatory factors might be associated with elevated BP variability during 24-hour ambulatory BP monitoring. Subjects were 140 healthy, normotensive adults. Inflammatory markers included C-reactive protein (CRP) and tumor necrosis factor-α (TNF-α). Bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 12 publications
1
23
0
2
Order By: Relevance
“…However, there is little evidence to demonstrate an association between inflammation and BPV in humans. Recently, Abramson et al demonstrated positive associations between markers of inflammation and BPV in healthy and normotensive adults (37). To our knowledge, this is the first report on the relationship between hs-CRP and 24-hr and awake systolic variability in African Americans.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is little evidence to demonstrate an association between inflammation and BPV in humans. Recently, Abramson et al demonstrated positive associations between markers of inflammation and BPV in healthy and normotensive adults (37). To our knowledge, this is the first report on the relationship between hs-CRP and 24-hr and awake systolic variability in African Americans.…”
Section: Discussionmentioning
confidence: 99%
“…Tatasciore et al [41] showed a significant relationship between hs-CRP and BP variability. Abramson et al [42] showed positive associations between markers of inflammation, including CRP and BP variability in healthy, normotensive adults, suggesting that inflammation might be one of the factors that promotes increased BP variability. Kaya et al [43] found higher CRP levels in patients whose nocturnal BP did not dip.…”
Section: Discussionmentioning
confidence: 99%
“…It was previously demonstrated that high BP is associated with inflammatory markers (19,39), and in recent studies a direct relationship between BP variability and inflammatory markers in normotensive adults (40) and hypertensive patients (41) was reported. Our data, showing significant relationships of sE-selectin and of hsCRP with BP variability, do not clarify the cause-effect relationships between BP variables and inflammation.…”
Section: Discussionmentioning
confidence: 99%